Communication Management of the Ngayogjazz Founders in Building a Sustainable Music Festival - Hendra Dwi Wibowo; Ismi Dwi Astuti Nurhaeni; Andre Noevi Rahmanto (Formosa Journal of Social Sciences (FJSS), 2023)
Festivals are tourism activities that are considered as one of the fastest growing forms of recreational activity. Ngayogjazz is a form of festival that has involved the local community since 2007 until now. Interestingly, Ngayogjazz claims that the festivals they regularly hold in tourist villages represent cultural events. Researchers want to focus on the communication management of Ngayogjazz founders in building a sustainable festival, besides this festival is a non-profit event. The author conducted a descriptive analysis to describe the problem in the form of a description. By conducting an analysis using management functions within the organization, namely planning, organizing, actuating, and controlling, the results of the research found that communication management in the Ngayogjazz community applies horizontal communication patterns with informal communication models